Development of polar order in a bent-core liquid crystal with a new sequence of two orthogonal smectic and an adjacent nematic phase - VIJ, JAGDISH KUMAR (My University, 2011)
A 4-cyanoresorcinol based bent-core liquid crystal shows a new phase sequence of two orthogonal smectic phases with short range (SmAP R) and long range (SmAP A) polar order beside a SmA-type cybotactic nematic phase (N CybA), leading to the phase sequence SmAP A-SmAP R-N CybA; this is of importance in LCD technology and provides a significant step forward towards polar and biaxial nematic phases
PUBLISHED
Keywords: polar order